The Relationship of Self-Efficacy and Self-Adaptation to Academic Performance of Nursing Students - Aulia Dewinta Makpal; Septiani Yuspin G. Reypaty; Theresia Kadore; Magda Fiske Rumambi; Iradewi (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: Student academic performance is very important for first-year students because it will determine their success in the lecture period. Factors that affect student academic performance include self-efficacy and self-adaptation. Objective: This study aimed to determine the relationship between self-efficacy and self-adaptation to student academic performance. Method: This study used correlational quantitative research methods. The population in this study were first-year nursing students at one of the Tangerang Private Universities, totaling 440 students. Data collection in this study will use a non-probability sampling technique, namely a consecutive sampling technique. The sample in this study was 220 students. The instruments used are the GSES (General Self Efficacy Scale) questionnaire, SACQ (Student Adjustment to Collage Questionnaire), and first-semester grade point average. The analysis in this study used univariate and bivariate analysis with the Chi-Square test. This research was conducted in January-April 2024. Result: The results showed a significant relationship between self-efficacy and academic performance with a p-value of 0.047 <0.005. However, there was no relationship between self-adaptation and academic performance, with a p-value of 0.575>0.05. The results of this study indicate that student academic performance can be influenced by self-efficacy but not by student self-adaptation. Conclusion It can be concluded that the higher students' self-efficacy, the better their academic performance, but self-adaptation does not affect students' high or low academic performance. Therefore, it is hoped that future researchers can develop research by using a broader measuring instrument to measure academic performance and find other variables that can affect student academic performance.